2013
DOI: 10.1002/lary.24485
|View full text |Cite
|
Sign up to set email alerts
|

Is cartilage conduction classified into air or bone conduction?

Abstract: Objectives/Hypothesis: The aim of this study was to establish the sound transmission characteristics of cartilage conduction proposed by Hosoi (2004), which is available by a vibration signal delivered to the aural cartilage from a transducer.Study Design: Experimental study. Method: Eight volunteers with normal hearing participated. Thresholds at frequencies of 0.5, 1, 2, and 4 kHz for air conduction, bone, and cartilage conductions were measured with and without an earplug. The sound pressure levels on the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 17 publications
4
67
1
Order By: Relevance
“…In an occluded ear canal, the intensity of the radiated airborne sound increases to decrease the thresholds in low frequency range [3]. Our previous study found the threshold decrease at 0.5 kHz for CC when the transducer was placed on the cavity of the ear canal [4]. The current results will reveal the difference in the contribution of Direct-AC and Cartilage-AC to the sound transmission among the locations.…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…In an occluded ear canal, the intensity of the radiated airborne sound increases to decrease the thresholds in low frequency range [3]. Our previous study found the threshold decrease at 0.5 kHz for CC when the transducer was placed on the cavity of the ear canal [4]. The current results will reveal the difference in the contribution of Direct-AC and Cartilage-AC to the sound transmission among the locations.…”
Section: Introductionmentioning
confidence: 64%
“…Fig. 2 shows the transducer whose property is described in the previous study [4]. The tragus (aural cartilage), pretragus (soft tissue), and mastoid (bone) locations for transducer placement are shown in Fig.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations